Analisis Pengelolaan Lahan Pertanian Pangan Berkelanjutan di Kabupaten Sambas - Romiyanto, Romiyanto; Agustine, Leony; Hazriani, Rini (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024), 2024)
This research aims to analyze management food farming areas in Sambas Regency. Sustainable food agricultural land protection is similar to the system and process for sustainable planning and determination, development, utilization, guidance, control and supervision of food agricultural land and its areas as stated in the Government Regulation of the Republic of Indonesia Number 30 of 2012 concerning Financing for Sustainable Food Agricultural Land Protection. The research method used was qualitative with descriptive analysis, with 2 informants, namely the village head and the head of the local service. The data sources were obtained from institutional data and previous research results with thematic maps based on a scale of 1:25,000 and direct measurements. Presentation of results in the form of tables, graphs, maps and brief descriptions of regional resources, especially in the agricultural sector. Initial analysis is carried out by individual consultants, a mapping team of Agriculture Service officers and/or together with other Working Group members on the Raw Sawah Land (LBS) map. Initial analysis was carried out by comparing data between the 2019 ATR/BPN LBS with spatial data available in districts/cities in tables and spatially. The LP2B area of Sambas Regency identified in 2022 is ± 45,623.79 ha. Where the land area referred to is the sum of the permanent rice field area of ± 40,743.77 ha, plus food moorland from the 2019 LBS data of ± 749.18, as well as additional identified rice fields and moorland area of 4,130.83 Ha. The results of the RPLP2B research in Sambas Regency resulted in Sambas Regent Regulation Number 71 of 2022 concerning the Distribution and Area of Protection of Sustainable Food Agricultural Land, where the total area of KP2B reached 43,948.12 Ha, consisting of LCP2B of 4,946.95 Ha and LP2B of 39,001.17 Ha.   Keywords : Sambas, Sustainable food, Food agricultural, Monitoring.